GII.4 human norovirus and G8P[1] bovine-like rotavirus in oysters (Crassostrea gigas) from Argentina - Mozgovoj, Marina Valeria; Miño, Samuel; Barbieri, Elena Susana; Tort López, Fernando; Montero, M. Victoria; Frydman, Camila Ayelén; Cap, Mariana; Barón, Pedro José; Colina, R.; Matthijnssens, Jelle; Parreño, Viviana Gladys (Elsevier, 2022)
Bivalve mollusks have been widely recognized as an important source of foodborne virus. The aim of this work was to determine the presence of norovirus (NoV) and rotavirus (RVA) in Pacific cupped oyster (Crassostrea gigas) from Buenos Aires, Argentina. A total of 88 oyster were processed. 7% of pooled samples resulted positive for NoV GII by RT-qPCR. The nucleotide analysis showed that it was closely related to GII.4/Sydney. Regarding RVA, 21% were positive by RT-qPCR targeting the NSP3 gene. RVA from one pool was isolated in cell culture and infective viral particles were evidenced by immunofluorescence. The genotype constellation of RVA/Oyster-wt/Crassostrea gigas_BA/2015/G8P[1] isolated strain was G8-P[1]-I2-R2-C2-M2-A3-N2-T6-E2-H3, which has a bovine-like genome backbone. Notably, RVA possesses an E2 genotype which is different from the characteristic E12 genotype of RVA circulating in animal species from South America. Our findings evidence not only the presence of enteric viruses in oysters from Argentina, but most important the viability of RVA. This result pose the need to implement surveillance programs to prevent potential foodborne viral outbreaks due to the consumption of contaminated shellfish.